Tracking the state of the delay hyperchaotic Lü system using the coullet chaotic system via a single controller. Issue 5 (18th December 2014) - Zhou, Yan; Shi, Xuerong; Wang, Zuolei; Huang, Juanjuan; Tang, Keming; Yu, Jianjiang
Abstract : In this article, a partial synchronization scheme is proposed based on Lyapunov stability theory to track the signal of the delay hyperchaotic Lü system using the Coullet system based on only one single controller. The proposed tracking control design has two advantages: only one controller is adopted in our approach and it can allow us to drive the hyperchaotic system to a simple chaotic system even with uncertain parameters. Numerical simulation results are given to demonstrate the effectiveness and robustness of the proposed partial synchronization scheme. © 2014 Wiley Periodicals, Inc. Complexity 21: 125–130, 2016